2021
DOI: 10.1111/ijcp.14110
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID‐19 on lower urinary tract symptoms in elderly men

Abstract: Aims The COVID‐19 pandemic is the most important public health problem in 2020. Millions of people have been infected or died because of the outbreak. We know the common symptoms of the disease such as fever and cough. However, all symptoms and features of COVID‐19 are still were not known. We aimed to evaluate the change in lower urinary tract symptoms (LUTS) after COVID‐19 in men. Methods We prospectively assessed 94 patients with COVID‐19 during hospitalisation. The patients were divided into two groups acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…Our cohort was primarily composed of elderly patients, who often have pre-existing genitourinary (GU) symptoms, and therefore presents a confounding variable in the study. However, this is consistent with a prospective study where lower urinary tract symptoms (LUTS) were increased in elderly men during COVID-19 hospitalization as measured by the International Prostate Symptom Score (IPSS) [ 18 ]. Future studies will evaluate GU symptoms in younger adult patients to see if this is related to age in addition to SARS-CoV-2 infection, and at later time points post SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 90%
“…Our cohort was primarily composed of elderly patients, who often have pre-existing genitourinary (GU) symptoms, and therefore presents a confounding variable in the study. However, this is consistent with a prospective study where lower urinary tract symptoms (LUTS) were increased in elderly men during COVID-19 hospitalization as measured by the International Prostate Symptom Score (IPSS) [ 18 ]. Future studies will evaluate GU symptoms in younger adult patients to see if this is related to age in addition to SARS-CoV-2 infection, and at later time points post SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, several previous studies described the relationship between psychological stress and the development of abnormal urinary tract signs and symptoms [56,57]. Although few recent reports in the literature showed that COVID-19 infection itself can cause symptoms of urinary tract infection [58][59][60], no study has investigated the association of COVID-19-related psychological distress with urinary tract health. Stress stimulates hypothalamic-pituitary-adrenal (HPA) and sympathetic-adrenal-medullary (SAM) axes.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the urinary isolates, the culture positivity increased to almost double (15% versus 8.3%) during the pandemic in comparison to previous year. A study by Can O et al showed that urine tract infections were significantly increased in elderly patients after COVID-19 infection [ 47 , 48 ]. Escherichia coli remained the most common pathogen followed by Enterococcus, Staphylococcus and Klebsiella pneumoniae in the urine samples of the COVID patients.…”
Section: Discussionmentioning
confidence: 99%